The Impact of Specific versus General Art Expertise on Art Experiences – The Case of the Sistine Chapel. - Lidegaard, Christina; Bille, Trine; Baldin, Andrea (Journal of Arts Management, Law & Society, 2022)
From the literature on art experience, we know that art experts and non-art experts have different cognitive information processes when encountering an artwork, but we don't know how this difference might influence the art experience. The purpose of this article is to test how expertise affects art experiences. Expertise is measured on several dimensions, one of them being the level of knowledge on the specific artwork, which is a new contribution to the literature. Our case is the Sistine Chapel at the Vatican Museum in Italy where the investigations took place in a real museum context.